Isolated Subclavian Vein Injury: A Rare and High Mortality Case - Sahin Iscan; Mustafa Etli; Ozgur Gursu; Esra Eker; Helin El Kilic (Case Reports in Vascular Medicine)
Isolated subclavian vein injuries are rarely seen without concomitant arterial injury, bone fracture, damage to brachial plexus, and thoracal traumas. Our case was brought to the emergency service 6 hours after he had been shot at the shoulder with a firearm. After detection of extravasation from the left axillary and subclavian vein on arteriographic and venographic examinations, he was operated on. An autogenous saphenous vein graft was interposed between subclavian and axillary veins. Cardiac arrest developed twice because of hypovolemia, which was resolved with medical therapy. Subclavian vein injuries have a more mortal course when compared with the injuries to the subclavian arteries. Its most important reason is excessive blood loss and air embolism because of delayed arrival to hospital. As is the case in all vascular injuries, angiography is the most important diagnostic examination. If the general health state of the patient permits, arteriography and venography should be performed in patients potentially exposed to vascular injuries. In patients with extreme blood loss and deteriorated health state, direct surgical exploration of the injury site, containment of the bleeding, and venous repair are life-saving approaches.